Case Study of The Divine Shepherdess Painting - Megan Crouch (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This study focuses on the historical significance of The Divine Shepherdess, a unique type of portable rolled “sarga” painting from the Carmel Mission in Carmel, California. The painting was used in missionary work during the Spanish Colonial period in New Spain (1492-1821). A technical description of the painting’s construction materials and conservation issues are presented. The treatment plan that was implemented for the painting’s active mold growth is described, and an additional case study involving mold abatement for a painting is included.